CONVAS2: A program for the merging of diffraction data - Rowles, Matthew (International Centre for Diffraction Data, 2010)
A computer program is presented that allows for the merging of diffraction patterns collected at multiple positions on the Powder Diffraction beamline of the Australian Synchrotron. It is also generally applicable to detector systems based on other modular detectors. The program allows for the interpolation of data to a constant 2? step size and to normalise intensities to beam current and/or monitor count rate.